A toolkit for decolonizing global emergency medicine education - Dozois, Adeline; González Marqués, Catalina; Thilakasiri, Kaushila; Adeyeye, Adebisi Anthonia; Leanza, Joseph; Rybarczyk, Megan; Depp, Timothy; Wieland, Travis; Karim, Naz; Muchatuta, Monalisa; Ali, Fahad; Amer, Ahmed; et al. (Frontiers in Education, 2023)
One of the tenets of global emergency medicine (GEM) is to create equitable relationships between highresource and resource-denied countries to promote emergency care for all. Health interventions proposed by those working in GEM too often lack input from local and indigenous communities result in "voluntourism", research authorship inequity, under-representation and under-valuation of technical expertise and lived experience of leaders from resource-denied countries. We present a decolonization toolkit with specific recommendations that target and disrupt counter-productive power dynamics in GEM education.We held a workshop at the 2022 Society for Academic Emergency Medicine Annual Meeting to collectively develop strategies to address inequalities and increase diversity in GEM education. GEM practitioners were divided into small groups representing five thematic areas and asked to identify specific action items to address inequities related to their theme. Following the workshop, a group of authors reviewed small group responses and data was divided into themed qualitative matrices and recommendations were revised based on targeted literature review.Five thematic areas discussed included access, awareness and cultural humility, language, representation and recognition. Specific recommendations and action items were created to address inequities related to these themes which can be applied by individuals and institutions in both HICs and LMICs.Despite being a relatively new academic discipline, GEM has replicated colonial structures that are prevalent in global health. However, using targeted recommendations described in our toolkit, individuals and institutions can build a new framework for GEM that actively combats structural vulnerabilities and academic inequities.